1992
DOI: 10.1007/bf00055514
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ethylene on proliferation and growth of rose shoot cultures

Abstract: Ethylene accumulation in four different rose in vitro culture containers was evaluated. Multiplication rate was the highest, and axes most elongated, in the two containers where ethylene accumulation was limited. Pulse treatments of ethylene at various concentrations enhanced proliferation depending on concentration (5 ppm generally was the most favourable) and time of application, while reducing elongation of the shoots. An ethylene trap in the flask atmospheres of the cultures reduced rose shoot proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Moreover, in aerated flasks, the number of shoots, leaf expansion and the number of leaves increased. Kevers et al (1992) showed that the multiplication rate and elongation of roses were higher in container types where ethylene accumulation was limited, however pulse treatments with C 2 H 4 during the first weeks of culture could enhance proliferation. Accumulation of CO 2 and C 2 H 4 during the first 10-15 days of Pinus radiata cultures promoted morphogenesis, while excessive accumulation after the initiation of buds caused some degree of dedifferentiation (Kumar et al, 1987).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, in aerated flasks, the number of shoots, leaf expansion and the number of leaves increased. Kevers et al (1992) showed that the multiplication rate and elongation of roses were higher in container types where ethylene accumulation was limited, however pulse treatments with C 2 H 4 during the first weeks of culture could enhance proliferation. Accumulation of CO 2 and C 2 H 4 during the first 10-15 days of Pinus radiata cultures promoted morphogenesis, while excessive accumulation after the initiation of buds caused some degree of dedifferentiation (Kumar et al, 1987).…”
Section: Resultsmentioning
confidence: 97%
“…In the given context, particular attention should be paid to the gaseous plant hormone ethylene, since Panizza et al [21], working with the in vitro culture of lavandin, have reported on the essential role of ethylene in cytokinin-inducible shoot proliferation. Although the exact levels of ethylene gas inside the culture tubes were not measured during the present study, the fact that additional sealing of culture vessels lead to increased amounts of accumulated ethylene is thoroughly established by other plant tissue culturists [14]. Thus, increased shoot proliferation under the conditions of reduced ventilation might be related to the reported ability of ethylene to cause defects in apical dominance through the decrease of auxin to cytokinin ratio [12].…”
Section: Methodsmentioning
confidence: 83%
“…This indicated that the trace amount of ethylene (presumably below 0.02 ppm) promoted EF. Kevers et al (1992) pointed out that ethylene inhibits shoot growth. Pulse treatment of C 2 H 4 enhanced proliferation depending on the concentration and time of application.…”
Section: Effects Of Individual Gas Componentsmentioning
confidence: 98%